Kesepian dan Regulasi Emosi pada Emerging Adulthood - Theja, Vanessa; Witarso, Laurentius Sandi (Fakultas Psikologi Universitas Sanata Dharma, 2023)
Abstract. Emerging adulthood is marked by the stage of experiencing intimacy vs isolation where they need to establish intimate relationships with their surroundings. Failure in establishing close relationships with those around him can make they feel lonely and will experience a variety of negative emotions. Emotion regulation is one way for individuals to control the emotions. Research on loneliness and emotion regulation needs to be studied further because there is a lot of focus on elderly subjects. The purpose of this study was to determine the relationship between loneliness and emotion regulation including cognitive reappraisal and expressive suppression on early adulthood individuals. The research was conducted using a quantitative method with a correlational design. Participants in this study are 138 people with an age range of 18-25 years. Researchers used the convenience sampling method and used the third version of the UCLA Loneliness Scale and the Emotion Regulation Questionnaire (ERQ). Data were analyzed using Pearson's correlation to examine the correlation between the two variables. The results showed that loneliness in early adulthood was correlated with expressive suppression (r = 0.35, n = 138, p 0.05, two-tailed). Early adulthood individuals tend to use expressive suppression as an emotion regulation strategy when experiencing loneliness. Meanwhile, loneliness did not correlate with cognitive reappraisal because it is suspected that individuals tend to have good well-being (r = 0.05, n = 138, p 0.05, two-tailed). Future research can examine other factors that can influence the relationship between the two variables in early adulthood.